1993
DOI: 10.1111/j.1471-0528.1993.tb15233.x
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective analysis of platelet numbers and volumes in normal pregnancy and in pre‐eclampsia

Abstract: Objective To determine the distribution of platelet volumes and numbers through pregnancy, and to compare these to changes in platelet volumes and numbers in women with pre‐eclampsia. Subjects Four hundred twenty‐eight women with normal pregnancy from whom four or more platelet measurements were available were identified. 74 women with pre‐eclampsia (blood pressure 140/90 mmHg, at least 0.5g protein/24 h urine collection) from whom platelet measurements were available between 27 and 30 weeks of ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

1995
1995
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(25 citation statements)
references
References 15 publications
(23 reference statements)
1
24
0
Order By: Relevance
“…Platelet microcytosis is a characteristic of the Wiskott^Aldrich syndrome (Thrasher et al 1998). Platelet macrocytosis is associated with Alports's syndrome (Patterson 1997) and elevated MPV with an increased risk of pre-eclampsia (Ahmed et al 1993). The MPV values for both sexes are quite close and unlikely to in£uence the di¡erentiation of microcytic or macrocytic platelets from normal.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…Platelet microcytosis is a characteristic of the Wiskott^Aldrich syndrome (Thrasher et al 1998). Platelet macrocytosis is associated with Alports's syndrome (Patterson 1997) and elevated MPV with an increased risk of pre-eclampsia (Ahmed et al 1993). The MPV values for both sexes are quite close and unlikely to in£uence the di¡erentiation of microcytic or macrocytic platelets from normal.…”
Section: Discussionmentioning
confidence: 64%
“…This has made an increasing number of parameters routinely available and generated data that were not previously available. In addition to the platelet count, the mean platelet volume has been suggested as a useful parameter (Ahmed et al 1993;Howarth et al 1999). The introduction of the Bayer ADVIA TM 120 (Bayer, USA) analyser has increased the range of platelet data that can be derived during the full blood count (FBC).…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, Dundar et al [22] compared preeclamptic women with normal pregnant women and showed a statistically significant increase in MPV levels just 4.6 weeks before the occurrence of preeclampsia symptoms. However, in contrast to these data, it was emphasized that MPV values may also be higher in normal pregnancies and just making a MPV screening test may be insufficient [18,19]. In conclusion, the reason for thrombocytopenia occurring in preeclamptic mothers is still unknown.…”
Section: Discussionmentioning
confidence: 97%
“…It is well known that the higher MPV seen in normal pregnancies depends on the increased platelet formation [5,6,18,19]. Despite this, researches made to compare the MPV and platelet numbers of the preeclamptic mothers with normal pregnancies have shown different results.…”
Section: Discussionmentioning
confidence: 98%
“…The MPV remained stable until 35 weeks gestation and rose dramatically thereafter. Ahmed et al (15) studied the MPV in healthy pregnants. This quantity remained constant between the first trimester and the end of normal pregnancy.…”
Section: Groups Of Patientsmentioning
confidence: 99%